STUDI LITERATUR: PENGARUH KOMPETENSI, PENGALAMAN, DAN INDEPENDEN AUDITOR TERHADAP EFEKTIVITAS PELAKSANAAN PROSEDUR AUDIT INVESTIGATIF - Anita Eka Pratiwi; Tri Ratnawati (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2023)
This research aims to conduct a literature review of previous studies and by documenting various references on topics and related to the effectiveness of the implementation of investigative audit procedures. This research method uses a qualitative approach or can be called a literature study. The data used in this study are secondary data in the form of previous research journals. The results showed that there are three factors that influence the effectiveness of the implementation of investigative audit procedures, namely auditor ability, auditor experience, and auditor independence. Auditor ability, both in communication, analysis, and understanding of fraud detection techniques, has a significant influence on the results of investigative audits.